Global, regional, and national burden of ischemic heart disease attributable to secondhand smoke from 1990 to 2019 - Xinyue Yang; Zhiqiang Zhang; Jiayi Sun; Wenjuan Zhang (Tobacco Induced Diseases)
Introduction Assessing the burden of ischemic heart disease (IHD) attributable to secondhand smoke (SHS) exposure is crucial for informing evidence-based healthcare practices, prevention strategies, and resource allocation planning.